Mulher e patriarcado. Violência de gênero contra a mulher em Carangola – MG (2006-2018) - Cheim, Erika Oliveira Amorim Tannus (2019)
This work aims to analyze how patriarchy influences the behavior of men and women and how the type of local sociability determines the silencing of conjugal and domestic violence in the city of Carangola, located in Zona da Mata, state of Minas Gerais, and which has aspects of countryside places. Regarding methodological aspects, this study has combined qualitative and quantitative methodologies, as this methodological approach has been adopted by a growing community of social science researchers and opposes the antithetical idea between the two methods. Ten women who experienced contexts of conjugal and domestic violence were interviewed, and 376 closed questionnaires were applied in different parts of Carangola city in the same period in order to know the reality of violence against women and find unreported/not denounced cases. The indication of the majority of respondents in the study was intermediated by the Specialized Reference Center for Social Assistance (CREAS), as the municipality does not have a Specialized Police Station for Women (DEAM). It was decided to access the CREAS service network, not because we believed in the judicialization of the cases, but because we believed that this institution engenders a support network to face violence, fundamental against the isolation that makes even more difficult the situation of women in Carangola. Because it is a city in the interior of Minas Gerais, access to specialized care services becomes more difficult, especially when it comes to public social assistance. For the application of the questionnaires, a sample calculation was performed, considering the local female population, estimated by the IBGE, in 16,604 women. The ten women in the study group narrated their experiences in violent marital relationships, most of whom experienced psychological and subtle violence. Among the ten cases studied there are also reports of physical, moral, patrimonial and sexual violence committed by the partners and also two attempts of femicide. The narratives point to aspects that confirm the presence of male domination in the marital relationships of the interviewees. Regarding the data produced by the survey, it was found that 69% of the women who participated in the survey had suffered some kind of domestic or marital violence. The city’s kind of sociability corroborates the strict local patriarchal codes still embedded in Carangolean families, making women hostage to violent marital relations in the name of preserving the ideal of happy marriage.